Breaking the “Fourth Wall” in Qualitative Research: Participant-Led Digital Data Construction - Boivin, Nettie; CohenMiller, A. S. (Qualitative Report, 2018)
This article reconstructs the typical researcher-participant focus - where the participants are doing for us - instead we followed the participants’ lead in the construction of research. Using a qualitative literacy event case study as an example, we describe how participants unexpectedly co-constructed knowledge through a participant-led digital data collection. In this theoretical article, we provide an explanation of the original study, which used observations, semi-structured interviews, and home visits as a collective qualitative case study on parental participation in social literacy practices. The original investigation led to the important shift that occurred in participant-researcher roles. In this article, using an ethnographic perspective, we explain how unexpected digital data creations created by participants’ family members allowed for enhanced equity between researcher and participant through changing the research dynamic, hearing and seeing participant voice previously unavailable. Situated within socio-cultural construction and the concept of Diderot’s concept of the fourth wall (the invisible barrier between audience and actor), we explain how these new insights provide opportunities for other qualitative researchers to enhance their practices through an ontological shift, intentionally “breaking the fourth wall of research” to integrate participant co-construction of knowledge...
Keywords: qualitative research; fourth wall; ethnography; community of learning; co-constructed knowledge